Genetic Analysis of Floral Symmetry Transition in African Violet Suggests the Involvement of Trans-acting Factor for CYCLOIDEA Expression Shifts - Hsu, Hui-Ju; He, Cheng-Wen; Kuo, Wen-Hsi; Hsin, Kuan-Ting; Lu, Jing-Yi; Pan, Zhao-Jun; Wang, Chun-Neng (Frontiers in Plant Science, 2018)
With the growing demand for its ornamental uses, the African violet (Saintpaulia ionantha) has been popular owing to its variations in color, shape and its rapid responses to artificial selection. Wild type African violet (WT) is characterized by flowers with bilateral symmetry yet reversals showing radially symmetrical flowers such as dorsalized actinomorphic (DA) and ventralized actinomorphic (VA) peloria are common. Genetic crosses among WT, DA, and VA revealed that these floral symmetry transitions are likely to be controlled by three alleles at a single locus in which the levels of dominance are in a hierarchical fashion. To investigate whether the floral symmetry gene was responsible for these reversals, orthologs of CYCLOIDEA (CYC) were isolated and their expressions correlated to floral symmetry transitions. Quantitative RT-PCR and in situ results indicated that dorsal-specific SiCYC1s expression in WT S. ionantha (SCYC1A and SiCYC1B) shifted in DA with a heterotopically extended expression to all petals, but in VA, SiCYC1s' dorsally specific expressions were greatly reduced. Selection signature analysis revealed that the major high-expressed copy of SCYC1A had been constrained under purifying selection, whereas the low-expressed helper SiCYC1B appeared to be relaxed under purifying selection after the duplication into SCYC1A and SiCYC1B. Heterologous expression of SCYC1A in Arabdiopsis showed petal growth retardation which was attributed to limited cell proliferation. While expression shifts of SCYC1A and SiCYC1B correlate perfectly to the resulting symmetry phenotype transitions in F1s of WT and DA, there is no certain allelic combination of inherited SiCYC1s associated with specific symmetry phenotypes. This floral transition indicates that although the expression shifts of SCYC1A/1B are responsible for the two contrasting actinomorphic reversals in African violet, they are likely to be controlled by upstream trans-acting factors or epigenetic regulations.